Rights in the Era of a Climate Change: Contemplating the Limits of Human Rights as Instruments of Pressure for the Planetary Cause .......... 9 (Fundamental Rights and Climate Change: Exploring New Perspectives and Corresponding Remedies, 2025)
One of the ways to address a “triple planetary crisis” (climate change, biodiversity loss, toxic pollution) consists in challenging existing legal frameworks, principles and remedies. The aim of this chapter is first, to contemplate, against the background of normative, judicial and ethical developments, both the impact of climate litigation on human rights’ architecture and also possible ways forward in the process of development of rights as instruments of pressure in a global attitude to tackle climate change. Secondly, current developments in the environmental and climate field of the EU legal order from a constitutional perspective are addressed, including the impact of the ECtHR Klimaseniorinnen judgement on the EU legal framework. Whilst the EU Courts are under pressure of an irrefutable link between human rights and the climate, the limits of judicial creativity should trigger a new debate about the feasibility of environmental rights in the EU legal order at large.